Adoption and effectiveness of de-escalated radiation and endocrine therapy strategies for older women with low-risk breast cancer. Issue 5 (June 2021) - Reeder-Hayes, Katherine E.; Wheeler, Stephanie B.; Meyer, Anne Marie; Baggett, Christopher D.; Zhou, Xi; Meng, Ke; Rotter, Jason; Zagar, Timothy
Abstract: Purpose: Recent clinical trials support de-escalation of adjuvant radiation therapy following lumpectomy in some older women with low-risk HR+ breast cancers planning to take endocrine therapy. The adoption of these findings into clinical practice, and the effectiveness of de-escalated therapy in real-world populations, remain under investigation. Materials and methods: We evaluated use of adjuvant radiation therapy and/or endocrine therapy among older women with T1-2 node-negative, HR+ breast cancer in the United States between 2007 and 2011. The study included patients from the Surveillance, Epidemiology and End Results-Medicare linked database and the North Carolina Cancer Information and Population Health Resource database. Results: Radiation therapy was received by 65.5% of patients, with no decrease over time. Older women and those with T2 (compared to T1) tumors were less likely to receive radiation therapy. In propensity-adjusted analyses, both radiation therapy alone (HR 0.75, 95% CI 0.67–0.84) and radiation + endocrine therapy (HR 0.62, 95% CI 0.54–0.69) were associated with significantly lower recurrence risk compared to endocrine therapy alone. Non-adherence to endocrine therapy was common (37%) and similar across groups. With a median follow-up of 48 months (range 13–84), we were not able to detect an association of non-adherence with recurrence risk in endocrine therapy-containing treatment arms. Conclusion: Most older women with stage I HR+ breast cancers continue to receive radiation, at higher rates than patients with node-negative stage II tumors. These findings suggest that while multiple evidence-based treatment options exist in these patients, improvements are needed to ensure that radiation therapy is applied equitably and rationally.